Proyecto de factibilidad para la creación de un taller mecánico, de mantenimiento exprés, a vehículos livianos para el cantón San Miguel de los Bancos de la provincia de Pichincha - Monserrate López, Florencio Agustín (2015)
Ecuadorian society has progressed in parallel with other companies in business field, from the creation of family businesses to large companies due to various market opportunities offered by society in general. The entrepreneurial vision is important for productive field of society as it will help in the near future to a new economic recovery of the country, accepting certain changes that the sector in question demands competitively in each of the lines that units of production offered. This project aims DETERMINE THE TECHNICAL FEASIBILITY, ECONOMIC, FINANCIAL AND ADMINISTRATIVE A MECHANICAL MAINTENANCE WORKSHOP EXPRES, A LIGHT VEHICLES FOR SAN MIGUEL The CANTON BANKS OF THE PROVINCE OF PICHINCHA, leveraging existing resources in the town. To carry out research population segmentation that helped find the way to deal with the complex and diverse demands of the people was. For each of the requirements of market surveys to potential consumers and vendors of the town was applied. Emphasizing everything mentioned above this project was obtained as main results as follows: The service offered is designed according to quality standards and requirements. The market study in the Canton San Miguel de los Bancos, we determined that the proposed creation of a mechanical maintenance workshop express for light vehicles can and should be run by the results obtained in the analysis of demand, supply and level marketing this service. The implementation of the company will be located in the canton San Miguel de los Bancos in Bolivar and Pichincha streets and be provided with services essential for the normal functioning of the same. The financial evaluation presents the following results: According to the NPV of this project gives us a positive value of $ 34,618.12, indicating that the project is convenient run. For this project IRR is 30.03%, this being satisfactory value for the project. The time required to recover the original investment would be three years, three months and 28 days (three years - 3 months - 28 days). The project cost benefit ratio is 1.19 this means that for every dollar invested company will get 19 cents of profit. For this project, the sensitivity values are less than one, thus not affecting the project changes in costs and revenues increased 17% and decreased by 13%, respectively, ie the project is not sensitive to these changes. Careful completion of each stage based on the results of this investment project demonstrates the feasibility feasibility of execution, largely filling the expectations of prospective consumers